PENGARUH KONSENTRASI MADU TRIGONA TERHADAP MUTU YOGHURT UBI JALAR ORANGE (Ipomoea batatas L.): The Effect of Trigona Honey Concentration on the Quality of Orange Sweet Potato Yoghurt (Ipomoea batatas L.) - Putri Putri Ningrum; Nazaruddin Nazaruddin; moegiratul amaro (Pro Food, 2022)
This study aims to determine the effect of trigona honey concentration on the quality of orange sweet potato yogurt (Ipomoea batatas L.). The method used in this study was an experimental method with a single factor Completely Randomized Design (CRD), the addition of 6 treatments of trigona honey consisting of 0%, 2.5%, 5%, 7.5%, 10% and 12.5%. Parameters observed were total lactic acid bacteria (LAB), total lactic acid, pH value, viscosity, color, aroma, taste and texture. Observational data were analyzed by analysis of variance at 5% significance level using Co-Stat software version 6.311. If there a significant difference, a further test is carried out with the Honest Significant Difference (BNJ) follow-up test for microbiological, chemical, physical and organoleptic parameters. The results showed that the addition of trigona honey had significantly different effects on total lactic acid, degree of acidity (pH), total lactic acid bacteria (LAB), viscosity, and organoleptic properties of texture (scoring and hedonic), taste (scoring and hedonic) and aroma (scoring). Orange sweet potato yogurt with the addition of 10% trigona honey was the best treatment based on a total LAB value of 9.65 log CFU/mL, total lactic acid 0.83%, degree of acidity (pH) of 4.21, viscosity of 3373 cP and both of organoleptic scoring and hedonic had results that were acceptable by the panelists both on the parameters of aroma, taste, color and texture that were suitable.